Transport, metabolism, cytotoxicity and effects of novel taxanes on the cell cycle in MDA-MB-435 and NCI/ADR-RES cells - Ehrlichová, Marie; Ojima, Iwao; Chen, Jin; Václavíková, Radka; Němcová-Fürstová, Vlasta; Vobořilová, Jana; Simek, Petr; Horský, Stanislav; Souček, Pavel; Kovář, Jan; Brabec, Marek; Gut, Ivan (Naunyn-Schmiedeberg's archives of pharmacology, 2012)
Resistance of tumours to taxanes causes chemotherapy failure in numerous patients. Resistance is partly due to the low tumour uptake of taxanes and their rapid metabolism. Structural modifications of taxanes can reduce their P-glycoprotein-related efflux or decrease metabolism and consequently increase taxane efficiency. This study compared cytotoxicity and effects of the cell cycle, transport and metabolism of novel taxanes SB-T-1102, SB-T-1103, SB-T-1214 and SB-T-1216, fluorinated SB-T-12851, SB-T-12852, SB-T-12853, SB-T-12854 and IDN5109 with paclitaxel in paclitaxel-sensitive (MDA-MB-435) and paclitaxel-resistant (NCI/ADR-RES) human cancer cells. We have shown before that NCI/ADR-RES cells were 1,000-fold less sensitive to paclitaxel than MDA-MB-435 cells in correspondence to P-glycoprotein overexpression and up to 20-fold lower uptake of the drug in the resistant cells. The uptake of novel taxanes was 1.2 to 3.8 times lower than that of paclitaxel in the MDA-MB-435 cells, but 1.5 to 6.5 times higher in NCI/ADR-RES cells. NCI/ADR-RES cells were correspondingly only 2- to 6.6-fold less sensitive than the MDA-MB-435 cells to novel taxanes. Both cell lines showed minimal metabolism of the novel taxanes which was therefore not responsible for their different sensitivity, the observed differences in their individual efficiency and higher effects than paclitaxel. All novel taxanes caused G(2)/M block of the cell cycle similar to paclitaxel, but lower at concentrations by order of magnitude. Thus, structural modifications of taxanes resulting in their decreased P-glycoprotein-related transport probably caused their higher efficiency than paclitaxel in multidrug-resistant NCI/ADR-RES tumour cells.
Keywords: Cell Survival; Chromatography, High Pressure Liquid; Drug Resistance, Multiple; vysokoúčinná kapalinová chromatografie; Humans; Cell Cycle; Antineoplastic Agents; lidé; chemorezistence; molekulární struktura; mnohočetná léková rezistence; Molecular Structure; Taxoids; taxoidy; nádorové buněčné linie; protinádorové látky; Cell Line, Tumor; Cell Culture Techniques; buněčný cyklus; Drug Resistance, Neoplasm; viabilita buněk; buněčné kultury